Recurrent bacterial infections, but not fungal infections, characterise patients with ELANE‐related neutropenia: a French Severe Chronic Neutropenia Registry study. (2nd August 2021) - Rotulo, Gioacchino A.; Plat, Geneviève; Beaupain, Blandine; Blanche, Stéphane; Moushous, Despina; Sicre de Fontbrune, Flore; Leblanc, Thierry; Renard, Cécile; Barlogis, Vincent; Vigue, Marie‐Gabrielle; Freycon, Claire; Piguet, Christophe; et al.
Summary: Among 143 patients with elastase, neutrophil‐expressed ( ELANE )‐related neutropenia enrolled in the French Severe Chronic Neutropenia Registry, 94 were classified as having severe chronic neutropenia (SCN) and 49 with cyclic neutropenia (CyN). Their infectious episodes were classified as severe, mild or oral, and analysed according to their natural occurrence without granulocyte‐colony stimulating factor (G‐CSF), on G‐CSF, after myelodysplasia/acute leukaemia or after haematopoietic stem‐cell transplantation. During the disease's natural history period (without G‐CSF; 1913 person‐years), 302, 957 and 754 severe, mild and oral infectious events, respectively, occurred. Among severe infections, cellulitis (48%) and pneumonia (38%) were the most common. Only 38% of episodes were microbiologically documented. The most frequent pathogens were Staphylococcus aureus (37·4%), Escherichia coli (20%) and Pseudomonas aeruginosa (16%), while fungal infections accounted for 1%. Profound neutropenia (<200/mm 3 ), high lymphocyte count (>3000/mm 3 ) and neutropenia subtype were associated with high risk of infection. Only the p.Gly214Arg variant (5% of the patients) was associated with infections but not the overall genotype. The first year of life was associated with the highest infection risk throughout life. G‐CSF therapy achieved lower ratios of serious or oral infectious event numbers per period but was less protective for patients requiring >10 µg/kg/day. Infections had permanent consequences in 33% of patients, most frequently edentulism.